(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article provides a comprehensive analysis of the role of resource taxes in the transition to a green economy using international experience and the practice of Uzbekistan. The study was conducted on the basis of official statistical data for the period 2022–2025, reports of international organizations (OECD, World Bank, UNDP, IEA), legislative documents of the Republic of Uzbekistan, and publications in scientific journals with a high impact factor. Comparative analysis, regression results, and systematic review of documents were used.